Toxicity of Military Chemical Sulfur Mustard on the Growth of Daphnia magna - Huong, Tran Thi Thu; Ngoc Toan, Vu; Le Dang Khoi, Ta (VNU Journal of Science: Earth and Environmental Sciences; Vol 39 No 1DO - 10.25073/2588-1094/vnuees.4894, 2023)
This study was conducted to assess the toxicity of the sulfur mustard military chemical to the growth and development of zooplankton Daphnia magna . D. magna is a group of crustaceans which have unique features such as virgin reproduction/ parthenogenesis form in a time, easy to identify and so they are usually used as a standard model organism for toxicity testing in aquatic environments. D. magna is exposed to a sulfur mustard stimulant at 0, 0.001, 0.005, 0.01, 0.05, 0.1, and 0.5 ppm. The results showed that sulfur mustard agent affected the growth and development of D. magna during the 24 and 48 h exposure. The highest toxicity was observed at the concentrations of 0.1 and 0.5 ppm with 100% mortality after both 24 and 48 h of exposure. At 0.001 to 0.05 ppm, the mortality rate changed from 6.7 to 30% at 24 h and this ratio increased to 10 and 100% at the concentration of 0.001 and 0.05 ppm after 48h, respectively. The LC50 values ​​recorded at 24 h and 48 h were 0.020 and 0.018 ppm, respectively. The results indicated that sulfur mustard can be toxic to the aquatic ecosystem and we need to take this into account when using this chemical group.